Pengembangan Potensi Wisata Bahari Di Kabupaten Tuban (Studi pada Dinas Perekonomian dan Pariwisata Kabupaten Tuban) - Yastynda, Surya Perwita (Jurnal Administrasi Publik, 2014)
Abstract: The Development of Nautical Tourism Potential in The Regency of Tuban (Studies in Dinas Perekonomian dan Pariwisata Kabupaten Tuban). Research on the development of nautical tourism potential in Tuban is grounded on the basis of decentralization, where an area is required to be able to govern administration and can develop their own regional development. Results of the analysis of the strategies that has been done by the Government in the development of Tuban nautical tourism potential has not yet been given a significant impact. For the Government of Tuban yet is totally committed and yet have adequate capacity in implementing the strategy and program development of nautical tourism potential. Tuban Regency Government deemed still not able to carry out the strategy of development of nautical tourism potential, this is due to the development of facilities and infrastructure has not been evenly distributed at each nautical attractions. Then the development of marketing and promotion carried out have not lasted to the maximum and the latter development of tourism partnerships are also not yet running to its full potential, proved to be not the existence of private parties or investors who helped in the development of nautical tourism objects in Tuban. Keywords: development, potential, nautical tourism Abstrak: Pengembangan Potensi Wisata Bahari di Kabupaten Tuban (Studi pada Dinas Perekonomian dan Pariwisata Kabupaten Tuban). Penelitian tentang Pengembangan potensi wisata bahari di Kabupaten Tuban ini dilandasi atas dasar desentralisasi, dimana suatu daerah dituntut untuk dapat mengatur jalannya pemerintahan serta dapat mengembangkan sendiri pembangunan daerah. Hasil analisis pengembangan yang telah dilakukan oleh Pemerintah Kabupaten Tuban dalam mengembangkan potensi wisata bahari belum memberikan dampak yang signifikan. Sebab Pemerintah Kabupaten Tuban belum benar-benar berkomitmen dan belum memiliki kapasitas yang memadai dalam melaksanakan strategi serta program pengembangan potensi wisata bahari. Pemerintah Kabupaten Tuban dianggap masih belum mampu untuk melaksanakan strategi pengembangan potensi wisata bahari, hal ini dikarenakan pengembangan sarana dan prasarana yang belum merata pada setiap objek wisata bahari. Kemudian pengembangan pemasaran dan promosi yang dilakukan belum berlangsung secara maksimal dan yang terakhir pengembangan kemitraan pariwisata juga belum berjalan secara maksimal, terbukti belum adanya dari pihak swasta atau investor yang membantu dalam pengembangan objek wisata bahari di Kabupaten Tuban. Kata kunci: pengembangan, potensi, wisata bahari